Balancing Environmental Protection and Administrative Fairness: A Critical Analysis of Indonesia’s Anti Eco-SLAPP Policy - Ilham Dwi Rafiqi; Elsa Diana; Ridwan Arifin (Administrative and Environtmental Law Review, 2026)
The Anti-Eco-SLAPP provision in Article 66 of Law No. 32 of 2009 on Environmental Protection and Management is designed to protect environmental defenders from retaliatory lawsuits and criminalization; however, its implementation continues to face significant technical and administrative challenges. This study critically assesses the effectiveness of Anti-Eco-SLAPP regulation, with particular focus on Regulation of the Minister of Environment and Forestry Number 10 of 2024, through the perspective of the General Principles of Good Governance. Employing a normative juridical approach, it analyzes relevant legal norms and policy frameworks and finds that, despite the promise of the regulatory design, its practical impact is weakened by complex administrative procedures and legal uncertainty. The study therefore recommends stronger inter-institutional integration, simplification of procedural requirements, and broader public participation to ensure effective protection for environmental defenders.